2021
DOI: 10.3389/fenvs.2021.710570
|View full text |Cite
|
Sign up to set email alerts
|

Using Geographic Information Systems and the Analytical Hierarchy Process for Delineating Erosion-Induced Land Degradation in the Middle Citarum Sub-Watershed, Indonesia

Abstract: Land degradation (LD) is an important issue worldwide because it affects food production and people’s welfare. Many factors cause land degradation, but in humid tropical areas, erosion is the main factor. More than 100 countries including Indonesia are affected by LD. Watershed management should be prioritized owing to budget constraints, while on the other side, the area affected by LD is very large compared to the size of the existing land area. The middle Citarum sub-watershed (MCSW) is one of the most degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
(35 reference statements)
0
10
1
1
Order By: Relevance
“…Judging from the level of erosion that occurs between 1.77 -284 tons/ha/year, the erosion conditions in central Citarum are equivalent to Adimihardja's research [15], which ranges from 35 to 220 tons/ha/year, which is the amount of erosion that occurs in the territory of Indonesia. Referring Ambarwulan's research [16] showed that the erosion class was smaller than the findings of Ambarwulan's research in the Middle Citarum watershed, where the erosion ranged from 0.87 to 495.30 tons/ha/years, which has a broader study area, thus enabling higher erosion values, which is derived from differences in land cover and a more diverse class of slopes…”
Section: Soil Erosionmentioning
confidence: 73%
“…Judging from the level of erosion that occurs between 1.77 -284 tons/ha/year, the erosion conditions in central Citarum are equivalent to Adimihardja's research [15], which ranges from 35 to 220 tons/ha/year, which is the amount of erosion that occurs in the territory of Indonesia. Referring Ambarwulan's research [16] showed that the erosion class was smaller than the findings of Ambarwulan's research in the Middle Citarum watershed, where the erosion ranged from 0.87 to 495.30 tons/ha/years, which has a broader study area, thus enabling higher erosion values, which is derived from differences in land cover and a more diverse class of slopes…”
Section: Soil Erosionmentioning
confidence: 73%
“…• Determine the positive ideal solution matrix and negative ideal solution Positive ideal solution matrix 𝐴 + calculated using Equation (11) with the rule of an attribute using Equation (13). Otherwise, the negative ideal solution is calculated using Equation ( 12) and the rule of Equation (14).…”
Section: • Calculating Information Entropymentioning
confidence: 99%
“…It is a valuable aspect of disaster risk analysis that indicators can continually develop. The integration of MCDA and the geographic information system (GIS) has widely been used in planning and environmental management [11]. The GeoTOPSIS MCDA module serves the integration of MCDA and GIS.…”
Section: Introductionmentioning
confidence: 99%
“…Many scienti c works employ approaches that make use of geotechnologies, such as geographic information systems and remote sensing, as an integrated tool for different types of geographic studies and methodologies (El Jazouli et al, 2017; Ambarwulan et al, 2021). Among these studies, different authors have used indicators and indexes as a tool for environmental analysis together with GIS, contributing with information on the state of degradation in water basins (Silva et al, 2022;Silva & Lima, 2017), and helping in the decision-making of public and private agencies.…”
Section: Introductionmentioning
confidence: 99%